Perubahan Wajah Vertikal Setelah 6 Bulan Perawatan Ortodontik Tetap - M. Shulchan Ardiansyah; Dena Chantika Arsarini (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2023)
Background: The use of fixed orthodontic appliances can change the vertical face due to the movement of the molars. A lateral cephalometric radiograph was used to assess the outcome of the treatment. Analysis of the vertical facial changes was performed by observing the changes of the MP-SN angle. Objective: The purpose of this study was to determine whether there were differences in the vertical face before and after 6 months of fixed orthodontic treatment using the Steiner method. Methods: This study used a case-control design comparing groups before and after 6 months of fixed orthodontic treatment. The sample in this study amounted to 5 people. The vertical measurement of the face is carried out at the MP-SN angle, namely the angle formed by the MP (Mandibular Plane – Go-Gn) line and the SN (Sella-Nasion) line. The data analysis was performed with the program SPSS Version 25. Result: There were no significant changes in the study (p>0.05). The average change is 1.2º. Of the 5 patients, 4 patients (80%) experienced a decrease in MP-SN angle, while 1 patient (20%) experienced an increase in the MP-SN angle. Conclusion: There was no significant change in facial vertical changes before and after 6 months of fixed orthodontic treatment at RSGM UMY. The decrease in the MP-SN angle is caused by the intrusion of the molars which causes the mandible to rotate counterclockwise. The increase in the MP-SN angle is due to the distalization of the molars, resulting in a clockwise rotation of the mandible.